Killer's choice - McBain, Ed, 1926-2005 (Armchair Detective Library, 1991)
Veteran Steve Carella teams up with a greenhorn detective Cotton Hawes to track down the vicious killer who murdered Annie Boone, a beautiful readhead with a complex past.